Disseminated Aspergillus lentulus Infection in a Heart Transplant Recipient: A Case Report . (11th March 2022) - Shivasabesan, Gowri; Logan, Bentley; Brennan, Xavier; Lau, Cindy; Vaze, Anagha; Bennett, Michael; Gorrie, Natasha; Mirdad, Feras; Deveza, Ricardo; Koo, Chung Mo; McCluskey, Peter; Macdonald, Peter; et al.
Abstract: We present the first published case of successfully treated disseminated Aspergillus lentulus infection in a solid organ transplant recipient with invasive pulmonary disease, endophthalmitis, and a cerebral abscess. This case highlights important challenges associated with treating A. lentulus, particularly regarding antifungal resistance and toxicities associated with long-term antifungal therapy.